Losing the Gains of the Past : The Welfare and Distributional Impacts of the Twin Crises in Iraq 2014 - Krishnan, Nandini; Olivieri, Sergio (World Bank, Washington, DC, 2016)
Iraq was plunged into two simultaneous crises in the second half of 2014, one driven by a sharp decline in oil prices, the other, by the war against the Islamic State in Iraq and Syria. The severity and recurrent nature of these crises demand a fast understanding and quantification of their welfare impact, which is critical for policy makers. This paper employs an innovative extension of the micro-simulation methodology to provide an ex ante estimate and analysis of the complex and dynamic poverty and distributional impact of the twin crises. The results show an almost complete erosion of the welfare gains of the past, with poverty falling back to 2007 levels and a 20 percent increase in the number of the poor. While the incidence of poverty is higher among internally displaced persons than the rest of the population (except in the Islamic State–affected governorates, where poverty is higher), internally displaced persons make up only a small proportion of Iraq's eight million poor in 2014. The rest comprise of households who already lived below the poverty line, or those who have fallen below the poverty line in the face of the massive economic disruptions the country is facing. The welfare impact of the crises varies widely across space, with the largest increases in poverty headcount rates in Kurdistan and the Islamic State–affected governorates. Yet, the poorest regions in the 2014 crisis scenario are the same as in 2012, the currently Islamic State–affected, and the South, with poverty rates of 40 and 30 percent, respectively. Although the simulated results are not strictly comparable to ex post micro data estimates, because of survey coverage constraints, overall the results are very much in line, particularly in Kurdistan and the South.